Tidal power trends and developments : proceedings of the 4th Conference on Tidal Power, organized by the Institution of Civil Engineers and held in London on 19-20 March, 1992. (Thomas Telford, 1992)
This volume covers works and studies on tidal power currently being undertaken, both nationally and internationally. Papers included cover the proposed Mersey barrage. The Department of Energy's continued variety of genetic work on tidal power and various overseas studies carried out by other experts are also detailed.